2018
DOI: 10.26773/smj.181009
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Tibia Length Measurements and Standing Height: A Prospective Regional Study among Adolescents in Southern Region of Kosovo

Abstract: The purpose of this research is to examine standing height in both Kosovan genders in the Southern Region as well as its association with tibia length, as an alternative to estimating standing height. A total of 225 individuals (120 male and 105 female) participated in this research. The anthropometric measurements were taken according to the protocol of ISAK. The relationships between body height and tibia length were determined using simple correlation coeffi cients at a ninety-fi ve percent confi dence inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 18 publications
2
4
0
Order By: Relevance
“…In our study, we found that when age was included as a covariate, the correlation strength between actual height and TL ( R 2 0⋅859) was slightly higher but not significantly different than when age was not included ( R 2 0⋅834). Our finding supports another study that included age as a covariate to the predictive equation based on TL which also found that age did not significantly affect the estimated height ( 13 ) . However, it can be said that both models had strong relationships with TL.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In our study, we found that when age was included as a covariate, the correlation strength between actual height and TL ( R 2 0⋅859) was slightly higher but not significantly different than when age was not included ( R 2 0⋅834). Our finding supports another study that included age as a covariate to the predictive equation based on TL which also found that age did not significantly affect the estimated height ( 13 ) . However, it can be said that both models had strong relationships with TL.…”
Section: Discussionsupporting
confidence: 90%
“…Lastly, it is important to note that the TL measurements can vary with ethnicity and race ( 13 , 18 ) . Therefore, it is crucial to consider these two factors when generalising the findings to the population.…”
Section: Discussionmentioning
confidence: 99%
“…Besides arm span, sitting height, foot length and tibia length [3,7,22,27] have proven to be good predictors of body height in our study. Hand length, using deterministic equations has been shown to be reliable predictors, especially about the body height of Kosovan adolescents of both genders.…”
Section: Discussionsupporting
confidence: 60%
“…A map of Kosovo is shown in Figure 1. A large number of studies has been conducted worldwide on body height to arm span ratios involving anthropometric parameters, using similar samples to the adolescent population of Kosovo in general [3,20,21], as well as on body height to foot length ratios [1], body height to sitting height ratios [7,22] and body height to tibia length ratios [23]. Based on the above research, it is critical for the population of Kosovo to have accurate information as well as body height to length of hand ratios, which are of great importance to medicine, sports, anthropology and other fields.…”
Section: Introductionmentioning
confidence: 99%
“…If we take into account that these are the most successful national teams, the small diff erence in height in comparison to the basketball players of the Serbian Super League (198,37), is both logical and expected. Based on this, we come to the conclusion that the selection is well done, and that, from the body height aspect, Serbians as a nation could meet the needs of modern basketball, having in mind that the general population respondents were among the tallest in Europe (Popović, Bjelica, Molnar, Jakšić, & Akpinar, 2013;Popović, Bjelica, Tanase, i Milašinović, 2015;Popović, Bjelica, Georgijev, Krivokapić, & Milašinović, 2017;Popovic, 2016;Popovic, 2017a;Bjelica, Popović, Kezunović, Petković, Jurak, & Grasgruber, 2012;Gardasevic, Masanovic, & Arifi , 2018;Arifi , Gardasevic, & Masanovic, 2018), which is an essential aspect during the selection process. Statistically signifi cant lower height of the players from Second League of Serbia (194,88) should not worry us because it is only logical that the players of lower quality leagues should have weaker morphological predispositions (Popović et al, 2010).…”
Section: Discussionmentioning
confidence: 99%